Innovations and future directions in English for specific purposes (ESP) : buku cenderamata - International Seminar on Innovations and Future Directions in English for Specific Purposes (ESP) (1995 : Johor Bahru, Johor); Universiti Teknologi Malaysia. Fakulti Pengurusan dan Pembangunan Sumber Manusia. Jabatan Bahasa Moden (Sekudai : FPPSM, UTM, 1995)
34